"دراسة تطبيقات التعليم العميق في مجال الذكاء الاصطناعي انجاز جهاز للكشف عن القناع الواقي " - خباز, فاطمة; باسي, ابتسام; بالعيد, أماني; بن حده, نورية (Université d'El Oued, 2022)
The law regulates the functioning of the country and guarantees the protection of the individual and the group. However, there are those who violate it, cause problems and impede the proper functioning of public and private order at the level of public and private institutions, so scientists and researchers, each in the fields, are working on finding practical and simple solutions that keep pace with technology instead of the traditional, complex and ineffective methods to avoid chaos and live in peace, and in In this note, we will try to develop a mechanism to detect face masks in public places and various institutions, and it will be an automated system placed in front of the entrances to institutions and hospitals to monitor people and take action with violators, which allows the wearer of a protective mask to pass and prevent violators using artificial intelligence applications and deep learning algorithms and using the SSD Mobile Net algorithm that is characterized Its ability to work well on devices with low computing power such as the Raspberry Pi. ينظم القانون سير البلاد ويضمن حماية الفرد والجماعة ورغم ذلك هناك من يخالفه ويتسبب في مشاكل وعرقلة السير الحسن للنظام العام والخاص على مستوى المؤسسات العامة والخاصة . لذلك يعمل العلماء والباحثون كل في المجالات على إيجاد حلول عملية وبسيطة تواكب التكنولوجيا بدلا من الطرق التقليدية المعقدة والغير فعالة لتجنب الفوضى والعيش بسلام ، وفي هذه المذكرة سنحاول تطوير آلية للكشف عن أقنعة الوجه في الأماكن العامة و مختلف المؤسسات و ستكون عبارة عن نظام آلي يوضع امام مداخل المؤسسات والمستشفيات لمراقبة الاشخاص و اجراء تدابير مع المخالفين تسمح لمرتدي القناع الواقي بالمرور وتمنع المخالفين وذلك باستعمال تطبيقات الذكاء الا صطناعي و خوارزميات التعليم العميق حيث اعتمدنا في هذا العمل التطبيقي على تدريب نموذج خاص بنا باستخدام الشبكات العصبية التلافيفية CNN لتحليل الصور والتعرف على الأشخاص و باستخدام خوارزمية SSD Mobile Net التي تتميز بسرعتها وامكانيتها للعمل على الأجهزة ذات الطاقة الطاقة الحسابية المنخفضة كالمتحكم .Raspberry Pi
مذكرات ماستر تخصص اتصالات
Keywords: ": Artificial intelligence, Deep learning, Raspberry Pi, SSD Mobile Net, Convolutional Neural Networks (CNN). "; ": الذكاء الاصطناعي ، التعليم العميق ، Raspberry Pi ،SSD Mobile Net ، الشبكات العصبية التلافيفية CNN . "